Proceedings of the 2nd International Conference on Uncertainty Quantification in Computational Sciences and Engineering (UNCECO 2017
DOI: 10.7712/120217.5350.17021
|View full text |Cite
|
Sign up to set email alerts
|

Operational Modal Analysis of Brodie Tower Using a Bayesian Approach

Abstract: Abstract. This paper presents a full-scale ambient vibration test and modal identification of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Systems from Guralp and GeoSIG provide this capability and the latter was deployed for ambient vibration testing of Humber Bridge in 2008 [24]. In the absence of a GPS signal, precision clocks can be used to synchronise recorders [25][26][27] but these are usually for high-end applications, and there is justification for low-cost devices with limited capabilities and simple operation in certain circumstance. The aim of this paper is to show the capabilities and limitations of such a system.…”
Section: Wireless Sensing For Civil Engineering Structuresmentioning
confidence: 99%
“…Systems from Guralp and GeoSIG provide this capability and the latter was deployed for ambient vibration testing of Humber Bridge in 2008 [24]. In the absence of a GPS signal, precision clocks can be used to synchronise recorders [25][26][27] but these are usually for high-end applications, and there is justification for low-cost devices with limited capabilities and simple operation in certain circumstance. The aim of this paper is to show the capabilities and limitations of such a system.…”
Section: Wireless Sensing For Civil Engineering Structuresmentioning
confidence: 99%
“…Allowing modal properties other than mode shapes to vary in different setups, it provides a fundamental means to process the information in the multiple measurements and make inference for the modal properties in a manner strictly consistent with modelling assumptions and probability logic. The comparisons between the Bayesian and post-identification methods [25,26] revealed that when the data quality is high in all setups the quality of global mode shapes is high and insensitive to the choice of method, e.g., be it local or global (least squares), Bayesian or non-Bayesian.…”
Section: Introductionmentioning
confidence: 99%